Effects of water volume of drip irrigation on soil bacterial communities and its association with soil properties in jujube cultivation - Li, Zhaoyang; Yang, Yuhui; Liu, Jiangfan; Jiang, Wenge; Gao, Yang (Frontiers in Microbiology, 2024)
Drip irrigation (DI) is an effective water saving method for improving the crop growth in arid areas. Jujube is one of an important crop in Xinjiang, China, a area suffered by water scarcity and DI has been proven as a suitable mode for jujube cultivation. Soil bacterial community play a vital role in biogeochemical cycles to support the crop growth, and water content is considered as one of the important factors for them. However, limited research has explored the optimum irrigation strategies, such as water volume of DI, to maximize the benefits of jujube cultivation by regulating the soil bacterial communities. In this study, three different water volume of DI for jujube cultivation were established and significant lower jujube yield and soil available nutrients were observed in samples with low water amount. In addition, we discovered significant effects of the water amount of DI and jujube growth stages on soil bacterial communities. Based on the compare of samples among different growth stages and water amounts some growth stage related bacterial genera (Mycobacterium, Bradyrhizobium, and Bacillus) and water amount-related bacterial phyla (Chloroflexi, Nitrospirota, and Myxococcota) were recognized. Moreover, according to the results of null model, soil bacterial communities were governed by stochastic and deterministic processes under middle and low water volumes of DI, respectively. Finally, we deduced that middle water amount (600 mm) could be the optimal condition of DI for jujube cultivation because the higher jujube yield, deterministic assembly, and stronger correlations between soil properties and bacterial community under this condition. Our findings provide guidance for promoting the application of DI in jujube cultivation, and further research is needed to investigate the underlying mechanisms of soil bacterial community to promote the jujube yield.